Relation between the plastic instability and fracture of tensile tested Cu-Sn alloys investigated with the application of acoustic emission technique (Fracture and Structural Integrity, 2015)
The work concerns the application of the acoustic emission (AE) method in testing the mechanical properties of continuously cast industrial tin bronze CuSn6P, which reveals tendencies to instable plastic flow connected particularly with the Portevin-Le Chatelier (PLC) effect. The relations between the jerky flow connected with the PLC effect, AE intensity and the evolution of a fracture of the investigated alloy subjected to the tensile test at a strain rate (?? ) of about 1.2·10-3s-1 in the range of temperatures (20÷400?C) has been analyzed. It has been found that the highest intensity of the oscillation of stresses, corresponding to the instability of plastic deformation PLC occurred at 200?C, whereas the maximum of the AE activity is at about 200÷250?C. The brittle intergranular fracture starts in the range of equicohersive temperature (TE) of about 200?C. Plastic deformation of the investigated alloy in the range of the temperature of minimum plasticity, amounting to about 400?C, results in intercrystalline fractures on the entire surface of the stretched samples.
Keywords: Copper alloy; Portevin-Le Chatelier phenomenon; Intercrystalline fracture